UPAYA KERJA SAMA GURU DENGAN WALI SISWA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 4 PONOROGO - Faridah, Emi Zulfa; Karomah, Laila Rahmatul (INCARE, International Journal of Educational Resources, 2022)
Education has a function as a bridge between the individual, the professional and the whole community, as well as education is the responsibility of every parent, educator and community. In order to improve the quality of education available in the country, you need to work together. Close cooperation between teachers and parents is needed to build a reality that the quality of a child's education is optimally fulfilled, supported by a community environment that promotes the quality of education. The purpose of this study is to learn of the school's efforts to make a partnership with the guardian of the student body and the cooperation between the school and the guardian of the student body in improving education at public school 4 ponorogo. The method used in this study is qualitative descriptive. Data collection procedures through interviews and observations. Research shows that 1) the school's efforts to cooperate with the parents are by creating a positive school atmosphere, communicating with the parents, and providing opportunities for parents to engage in madrassa activities, 2) parenting, interpersonal communication and parenting.